Екологізація технологій вирощування сої в Степу України - Геллер, О. Й.; Geller, O.; Пашова, Валентина Трифонівна; Pashova, Valentina; Корбанюк, Р. А.; Korbanyuk, R.; Лемішко, Світлана Миколаївна; Lemishko, Svitlana (Дніпровський державний аграрно-економічний університет, 2015)
Доведено, що підвищення польової схожості, активізація процесів дихання і живлення сої за інкрустації насіння біопрепаратами і бішофітом позначається на підвищенні врожаю та його якості. При екологізації технологій вирощування сої в Степу перспективним є прийом інкрустації насіння сої біопрепаратом АКМ і бішофітом, що пов’язано з істотними змінами в процесі обміну речовин, перебудовою ряду метаболічних систем на генному рівні. Studying chemical fertilizers influence on growth, development, productivity and quality of soybean carried out in the steppes of ordinary chernozem humus on the less. Biologization technology and individual techniques is an important measure that can deter further reduction in soil fertility, stabilize production systems, reduce dependence on technological factors. Throughout combination with fertilization of crops lowest material and labor costs account for inlay biostimulyators seeds and micronutrients. Researched increase field germination processes of respiration and nutrition of soybean seeds with inlay and biological products bishofit that impact on improving yield and quality. Increase of grain was 3,5–4,0 kg/ha, the content of “raw” protein, protein, fat increased. At the greening of soybean growing technology in the steppe promising method inlay seeds biopreparation AKM and bishofit, due to significant changes in metabolism, the restructuring of a number of metabolic systems at the gene level.
Greening Technology soybean cultivation in the Steppe Ukraine
Keywords: соя; soy; біопрепарати; biopreparations; інкрустація; inlay; АКМ; АКМ; бішофіт; bischofite; “сирий” протеїн; “raw” protein; білок; protein